Tan Cheng Bock [Singapore, Member of Parliament] - Tan, Cheng Bock (Institutional Knowledge at Singapore Management University, 2015)
Former veteran People's Action Party Member of Parliament, presidential candidate Dr Tan Cheng Bock speaks his mind with DNA on his struggles during his school days, National Service, and what had motivated him to enter politics. He reveals his take on Foreign Talent, the Feedback Unit, and shares on the kind of society he hopes Singapore will become.